5% benzoyl peroxide is the most efficient in reducing the cutibacterium flora of the shoulder skin: a network meta-analysis - Viktor Weninger; Gergely Agócs; Luca Hergár; Szilárd Váncsa; Bence Hegedűs; Imre Szerb; Péter Hegyi; Gábor Skaliczki (EFORT Open Reviews, 2025)
Purpose: Our study aims to compare different perioperative treatments to reduce C. acnes, the most common causative agent of surgical site infections following shoulder surgery. Methods: A systematic search was performed in MEDLINE (PubMed), Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and the Web of Science for studies published up to October 20, 2022. We included randomized-controlled trails investigating the efficacy of different dermal preparation in reducing the C. acnes colonising the skin surface. The studies examined positive bacterial cultures before and after skin treatment. The included trials were able to compare seven different skin treatment methods. We performed a frequentist network meta-analysis and calculated pooled risk ratios (RRs) with 95% confidence interval (CI). Results: Our study could include comparisons of 946 different patients. The use of 5% benzoyl peroxide (BPO) and its combination with the antibiotic clindamycin was found to be the most effective in reducing C. acnes colonization on the skin (BPO 5% RR = 0.25, CI: 0.08–0.72, BPO with clindamycin RR = 0.25, CI: 0.04–1.50). Based on the rank plot, 5% BPO (P score: 0.808) was the most effective treatment, followed by BPO 5% with clindamycin (P score: 0.749). We could not perform a network meta-analysis regarding the efficacy of different dermal preparation in reducing C. acnes colonization on the dermis and in the joint. Conclusion: Cutibacterium colonization of the skin flora can be effectively reduced on the skin surface by the use of 5% BPO.